Manejo de Spodoptera frugiperda (J. E. Smith, 1797) em milho com plantas Bt, inseticidas químicos e Baculovirus - Giacomelli, Tiago (2021)
The fall armyworm, Spodoptera frugiperda (J. E. Smith 1797) (Lepidoptera: Noctuidae) is considered the main insect pest of corn (Zea mays) in Brazil. The control of this pest is carried out mainly with the use of Bt Plants (Bacillus thuringiensis) and chemical insecticides and, more recently, the use of biological insecticides has grown as a new alternative to be added to Integrated Pest Management. In order to evaluate the efficacy of Bt proteins expressed by some corn hybrids available on the market, as well as the interaction with the use of chemical and biological insecticides based on Baculovirus spodoptera for the control of this species, field experiments were carried out, with infestation natural of S. frugiperda, during two sowing seasons in the 2019/20 crop. Five Bt corn hybrids and one non-Bt corn hybrid were evaluated, in addition to 6 chemical insecticides and 2 biological insecticides. The evaluations were carried out at an interval of five days, attributing damage scores, according to the Davis Scale (1992), in addition to counting the number of plants attacked. For decision-making on insecticide applications, a control level was assigned whenever 10% of the evaluated plants had a damage score ≥ 3. In the first crop of the 2019/2020 season, DKB 290 (Cry1A.105/ Cry2Ab2/ Cry3Bb1) and Morgan 20A78 (Cry1F/ Cry1A.105/ Cry2Ab2) required four insecticidal applications, while Pioneer 32R22YHR (Cry1F/ Cry1Ab) and Pioneer 30F53R (non-Bt) required five insecticidal applications to mitigate S. frugiperda damage. In the second crop, DKB 290 and Morgan 20A78 required three to six insecticide applications, while Pioneer 32R22YHR and Pioneer 30F53R (non-Bt) required five to seven insecticide applications. On the other hand, in both cultures, Pioneer 30F53VYHR (Cry1Ab/ Cry1F/ Vip3Aa20) and Brevant 2401 (Cry1F/ Cry1A.105/ Cry2Ab2/ Vip3Aa20) did not require insecticidal applications, showing the efficiency of Vip toxins. Regarding the combination of chemical + biological insecticides, in the first crop, starting applications with Baculovirus spodoptera was more efficient, and in the Pioneer 30F53R corn hybrid the Baculovirus spodoptera + Exalt combination performed better, and in the corn hybrid Pioneer 32R22YHR the best combination was Baculovirus spodoptera + Exalt and Avatar. In the second crop, starting applications with chemical insecticides showed lower damage rates, because in both corn hybrids, the best combination was to start treatments using Exalt + Baculovirus spodoptera. Among the chemical insecticides used in this work, the ones that performed better were Exalt and Premio.